Relationships between physical performance and knee and hip osteoarthritis: findings from the European Project on Osteoarthritis (EPOSA). - Edwards, M; van der Pas, S; Denkinger, MD; Parsons, C; Jameson, K; Schaap, L; Zambon, S; Castell, M; Herbolsheimer, F; Nasell, H; Sanchez-Martinez, M; Otero, A; et al. (Oxford University Press, 2014)
BACKGROUND: poor physical performance (PP) is known to be associated with disability, lower quality of life and higher mortality rates. Knee and hip osteoarthritis (OA) might be expected to contribute to poor PP, through joint pain and restricted range of movement. Both clinical and self-reported OA are often used for large-scale community and epidemiological studies. OBJECTIVE: to examine the relationships between hip and knee OA and PP in a large data set comprising cohorts from six European countries. METHODS: a total of 2,942 men and women aged 65-85 years from the Germany, Italy, Netherlands, Spain, Sweden and the UK were recruited. Assessment included an interview and clinical assessment for OA. PP was determined from walking speed, chair rises and balance (range 0-12); low PP was defined as a score of ≤9. RESULTS: the mean (SD) age was 74.2 (5.1) years. Rates of self-reported OA were much higher than clinical OA. Advanced age, female gender, lower educational attainment, abstinence from alcohol and higher body mass index were independently associated with low PP. Clinical knee OA, hip OA or both were associated with a higher risk of low PP; OR (95% CI) 2.93 (2.36, 3.64), 3.79 (2.49, 5.76) and 7.22 (3.63, 14.38), respectively, with relationships robust to adjustment for the confounders above as well as pain. CONCLUSION: lower limb OA at the hip and knee is associated with low PP, and for clinical diagnosis relationships are robust to adjustment for pain. Those at highest risk have clinical OA at both sites.